The Reality of Using Cloud Computing in Information and Record Management in Oman - Elsawy, Elsayed Salah (Journal of Ecohumanism, 2024)
The aim of this study is to explore the main applications of cloud computing in records management and to understand the views of records managers on the use of these applications in Omani institutions. It aims to identify the benefits, potential challenges, and the proposed solutions associated with the implementation of cloud computing in records management. The study used the descriptive analytical approach and conducted surveys to collect data on the use of cloud computing applications to manage, store, and access records in Omani institutions. The study included the views of 105 records managers from 32 Omani institutions, including ministries, universities, and authorities. In addition, a focus group was formed consisting of 9 participants from various records departments in various Omani institutions, such as the Ministry of Justice and Legal Affairs, the Ministry of Finance, the Oman Oil Development Company, the Ministry of Higher Education, Research and Innovation, and others. The study found that the majority of records managers prefer that organizations provide cloud computing services themselves. The cloud applications most used among participants were email services, Microsoft Office, Google Apps, and Dropbox. The main record-related activities included exchanging records with other organizations, storing and archiving records, sharing files within departments, and email management. Records managers emphasized the need for training programs to enhance their skills in electronic archiving, cloud computing, and modern record management techniques. The study recommends raising awareness among relevant stakeholders, including records management professionals and organizational leaders, about cloud-based record management systems and their potential to improve efficiency. Additionally, it suggests aligning cloud solutions with Omani regulations concerning data protection and record retention. The study also recommends providing financial and technical support to records departments in institutions for the implementation of best practices in cloud-based record management systems, as these systems rely on information and communication technologies.